2016
DOI: 10.1155/2016/7615853
|View full text |Cite
|
Sign up to set email alerts
|

The Content and Bioavailability of Mineral Nutrients of Selected Wild and Traditional Edible Plants as Affected by Household Preparation Methods Practiced by Local Community in Benishangul Gumuz Regional State, Ethiopia

Abstract: Edible parts of some wild and traditional vegetables used by the Gumuz community, namely, Portulaca quadrifida, Dioscorea abyssinica, Abelmoschus esculentus, and Oxytenanthera abyssinica, were evaluated for their minerals composition and bioavailability. Mineral elements, namely, Ca, Fe, Zn, and Cu, were analyzed using Shimadzu atomic absorption spectrophotometer. Effects of household processing practices on the levels of mineral elements were evaluated and the bioavailability was predicted using antinutrient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
0
20
0
2
Order By: Relevance
“…The variations observed in the amount of calcium (9 to 13.7 mg/100g), potassium (383 to 683 mg/100g), iron (0.3 to 0.5 mg/100g) and magnesium (11.3 to 16.3 mg/100g) among the fried yam samples studied could be as a result of possible differences in varieties of yams studied as well as their cultivation conditions. Previous studies (Chandrasekara and Kumar, 2016;Hailu and Addis, 2016;Adepoju, 2012;Udensi et al 2008 and2010;Shajeela et al 2011;Akin-Idowu et al 2009) have shown similar trends of variation in minerals content of raw and processed yam varieties.…”
Section: Resultsmentioning
confidence: 52%
“…The variations observed in the amount of calcium (9 to 13.7 mg/100g), potassium (383 to 683 mg/100g), iron (0.3 to 0.5 mg/100g) and magnesium (11.3 to 16.3 mg/100g) among the fried yam samples studied could be as a result of possible differences in varieties of yams studied as well as their cultivation conditions. Previous studies (Chandrasekara and Kumar, 2016;Hailu and Addis, 2016;Adepoju, 2012;Udensi et al 2008 and2010;Shajeela et al 2011;Akin-Idowu et al 2009) have shown similar trends of variation in minerals content of raw and processed yam varieties.…”
Section: Resultsmentioning
confidence: 52%
“…ILVs grow as weeds in the wild or in cultivated areas, but have also been domesticated through semi-cultivation or cultivation [6]. In addition, ILVs thrive with minimal care, are inexpensive, easily accessible, easy to cook, and could play an important role in ensuring micronutrient supply [3,7,8,9,10]. ILVs with high concentrations of provitamin A carotenoids and iron could essentially contribute in the reduction of vitamin A and iron deficiencies in rural areas where the diet is low in animal source foods [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such nonconventional sources are directly related to biodiversity. Nature provides numerous wild edible-medicinal products, such as leaves, flowers, fruits, nuts, berries, stems, roots, and tubers (Chandrasekara and Kumar, 2016 ; Geng et al, 2016 ; Hailu and Addis, 2016 ; Keservani et al, 2016 ). Among these, roots and tubers come under the minor wild crops, having very less scientific documentation, although they play important roles to fight against food scarcity.…”
Section: Introductionmentioning
confidence: 99%